STUDIES OF PATHOLGICAL CHANGES OF LOCAL BREED CATTLE NATURALLY-INFECTED ‘ WITH FASCOIOLA GIGANTICA - A.A Makkawi , T.; D. Yohanna, S. (The Iraqi Journal of Veterinary Medicine, 1989)
This study was conducted to characterize the pathological changes caused by F. gigantica.The pathological changes were studied in samples collected from abattoir, which included, livers, gall badders and hepatic lymph nodes.The results indicate that the disease is endemic in Baghdad area and the areas around it. The incidence rate of this parasite increased in the beginning of winter and decreased to it's‘ lowest in April. The disease(Fascioliasis) was classified as acute and chronic.